Effects of Omega-3 Polyunsaturated Fatty Acids to The Serum Level of Interleukin-8, Percentage of Forced Expiratory Volume in 1 Second (%FEV1), and COPD Assesment Test Scores in Stable COPD Patients - Nisfi Angriani; Suradi Suradi; Yusup Subagio (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2017)
Backgorund: Cigarette smoke inhalation and the other exposure can cause of airway inflammatory and it was the most cause of chronic obstruction pulmonary desease (COPD) pathogenesis. The airway inflammatory will release cytokines proinflammation, one of them was interleukin (IL)-8. Omega-3 polyunsaturated fatty acids (PUFA) have anti-inflammatory effect and its can decrease cytokines production in COPD pathogenesis. Methods: This study aimed to analyze effects of omega 3 PUFAs on serum IL-8, %FEV1, and CAT score in stable COPD patients. Clinical trials of experimental with pretest and posttest designs were conducted of 32 stable COPD patients came to clinic in Dr. Moewardi Hospital Surakarta from December 2016 until February 2017. Samples were taken by consecutive sampling. Subjects were divided into two groups include the treatment group (n=16) received standard COPD therapy omega 3 PUFA 600mg/day and the control group (n=16) received only standard COPD therapy for 28 days. Results: There were significant difference (P=0.0001) towards decreased of serum IL-8 between treatment group (-3.56+5.32pg/ml) and control group (8.90+9.98pg/ml), increase difference were no significantly of %VEP1 value (P=0.473) between treatment group (7.02+7.17pg/ml) and control group (5.32+5.97pg/ml), decrease difference of CAT scores significantly (P=0.0001) between treatment group (-16.13+3.03pg/ml) and control group (-4.75+4.17pg/ml). Conclusions: Omega-3 PUFA may decrease airway inflammation with decrease serum IL-8 level significantly, increase of %FEV1 no significantly and improve the clinical symptoms of stable COPD by decreased CAT scores significantly in stable COPD patients. (J Respir Indo. 2017; 37(4): 265-77)